In Vivo SELEX of Single-Stranded Domains in the HIV-1 Leader RNA - van Bel, Nikki (American Society for Microbiology, 2014)
The 5′ untranslated leader region of the human immunodeficiency virus type 1 (HIV-1) RNA genome is a strongly conserved sequence that encodes several regulatory motifs important for viral replication. Most of these motifs are exposed as hairpin structures, including the dimerization initiation signal (DIS), the major splice donor site (SD), and the packaging signal (Ψ), which are connected by short single-stranded regions. Mutational analysis revealed many functions of these hairpins, but only a few studies have focused on the single-stranded purine-rich sequences. Using the in vivo SELEX (systematic evolution of ligands by exponential enrichment) approach, we probed the sequence space in these regions that is compatible with efficient HIV-1 replication and analyzed the impact on the RNA secondary structure of the leader RNA. Our results show a strong sequence requirement for the DIS hairpin flanking regions. We postulate that these sequences are important for the binding of specific protein factors that support leader RNA-mediated functions. The sequence between the SD and Ψ hairpins seems to have a less prominent role, despite the strong conservation of the stretch of 5 A residues in natural isolates. We hypothesize that this may reflect the subtle evolutionary pressure on HIV-1 to acquire an A-rich RNA genome. In silico analyses indicate that sequences are avoided in all 3 single-stranded domains that affect the local or overall leader RNA folding. IMPORTANCEin vivo